New approach for analysing the effect of minor and major solar cooker design changes: Influence of height trivet on the power of a funnel cooker - Apaolaza-Pagoaga, Xabier; Carrillo-Andrés, Antonio; Rodrigues-Ruivo, Celestino (Elsevier, 2021)
In present work, the power values of two funnel cookers were determined by following the standard ASAE S580.1 procedure and also a novel improved approach for better analysing the effect of minor design changes. This new approach is based on experimental side by side tests of the two cookers and it adopts a shorter time interval and a curve fitting based on the LOESS adjustment is adopted for the evaluation of the difference in power values of the different designs tested. The two funnel cookers were tested experimentally with a load ratio of 4 kg m2. The influence of the height of a trivet, from 0 to 100 mm, on the cooker power was evaluated. The estimated changes in power values due to the design changes were low but not negligible. As example, the power standardised increases 6 W when a height trivet of 25 mm is used respecting cooking operation without trivet. The novel approach is promising because it enables to determine the impact of minor design changes on the power of the cooker. The same analysis is not possible to be performed with the standard ASAE S580.1 procedure due to the uncontrollability of the weather conditions.
Keywords: Energía solar - Aplicaciones; Solar cooking; Funnel cooker; Experimental test; Side by side; Trivet